Heart Rate and Perceived Exertion Among Young Adult Obese Males During One-Handed Carrying. (September 2018) - Badawy, Mohamed; Schall, Mark C.; Gallagher, Sean; Sesek, Richard F.; Davis, Gerard A.
Obesity is an increasing problem across the globe that has been strongly associated with work-related injury. One-handed carrying is considered one of the most fatiguing methods of load carrying. The objective of this study was to examine the effects of obesity and load magnitude on heart rate and ratings of perceived exertion among young adult males during one-handed carrying. Load magnitude was observed to have a statistically significantly effect on heart rate and perceived exertion of the arm, back and whole body, whereas obesity was significant only for perceived exertion of the arm. The results suggest that young adult obese males can carry similar loads as young adult non-obese males without having a statistically significant increase in heart rate or perceived exertion. However, more research is needed to validate these results for longer distances and carrying times.